Draft whole-genome sequence of the antibiotic-producing soil isolate Pseudomonas sp. strain 250J - Molina-Santiago, Carlos; Udaondo, Zulema; Ramos, Juan-Luis (Wiley, 2014)
Bacteria of the genus Pseudomonas are becoming increasing well known for their ability to produce a wide range of antimicrobial compounds. In a largescale screening for antibiotic producers, we identified a soil isolate that uses 4-hydroxyphenylacetate as the sole carbon source, Pseudomonas sp. strain 250J, which produces cyclic lipodepsipeptides of the xantholysin family during the stationary phase of growth. The closest relatives of this strain are Pseudomonas mosselii, Pseudomonas soli and Pseudomonas entomophila. Sequencing of the 250J genome allowed us to find the genes relevant to antibiotic production, those which allow utilization of 4-hydroxyphenylacetate as a sole carbon source and a set of genes potentially involved in biocontrol.
Keywords: Genomas; Antibióticos; Pseudomonas; Genome sequencing